Variasi Bahasa Lisan Pedagang Kaki Lima di Pasar Bastiong (Suatu Tinjauan Sosiolinguistik) - Ismail Maulud; Ridwan Ridwan (Universitas Khairun, 2018)
Ternate town comes from multi-ethnic or from many other countries outside. They come to bring their language and culture itself, so in communicating with each other they usually use Indonesian language and Ternate Malay language or multilingual. In Bastiong Market, there is a lot of social community; like from Buginese, Makassar, Buton, Tidore, Ternate, Javanese, and Makianese. In daily communication between a buyer and a seller, they usually use the language that related to whom they speak to, as like; Ternate language, Ternate Malay language, Indonesian language, Java language, Bugis and Makassar language, Tidore language, and Makian language.Ã‚Â Ã‚Â The objective of this research is to find out and to explain more about the use of language variations that are used by the people in Bastiong Market. This research also finds out the factors that influence language variation in communicating with each other (buyer and seller).Ã‚Â The result of this research shows that there are several languages involved in the interaction among buyer and seller in Bastiong Market, namely Ternate language, Ternate Malay, Tidore, Bugis, Makassar, Buton, and Makian. Kata Kunci: Language Variation, Multilingual, speech, Seller and Buyer